The Influence of Trust, in Mediating Perceived of Risk, and Web Quality on Purchasing Decisions” (Study on Student Users of Online Shopping (Shopee) at Udinus - Tjahyono, Antonio Immanuel Surya; Mahmud, Mahmud (Journal of Economic Education, 2024)
Introduction: want to see the influence of Trust, Perceived of Risk, and Web Quality on purchasing decisions. The development of the world of business and trade, technology and its use for electronic trading or what we usually call e-commerce, namely trading information carried out using the internet. Indonesia is a very potential market in the development of e-commerce, followed by the growth rate of internet users in Indonesia, based on data obtained from purchasing products via the internet, 26% of respondents were inspired to make purchases via smartphone, 76% of respondents used smartphones to search for information before they make purchases, and 12% made purchases via smartphone. The level of confidence of people making transactions via online shopping may be greatly supported by the existence of the online Shopping Guarantee program, the perception of risks arising may also be slightly reduced. Because users feel they enjoy good activities by shopping online. This research is quantitative research, the sample in this research is 109 sampling techniques used in this research, namely random sampling. Web quality has a positive and significant influence on purchasing decisions and trust, while trust has a positive and significant influence on online purchasing decisions. Risk perception has a negative and significant influence on trust and purchasing decisions, where the higher the perceived risk felt by customers, the lower their trust and purchasing decisions in online shopping.